Guided Demonstration Method to Improve Students' Skills in Processing Banana - Widagdo, Andika Kuncoro; Handajani, Sri; Astuti, Nugrahani; Aini, Annisa Nur; Yuliana, Siti; Bahar, Asrul (TEKNOBUGA: Jurnal Teknologi Busana dan Boga, 2023)
This research describes the training process and results of banana processing through the demonstration method at MAN 2 Madiun. This research aims 1) to know the instructor's activities, 2) to find out the participants' activities, 3) to determine student learning outcomes, and 4) to find out the participants' responses to the training. This study used an experimental method with a pre-experimental research design model of a one-shot case study, observation as data collection techniques, and knowledge and skill tests. The process is documented. The research results are as follows: 1) The instructor's activities cover three aspects, namely the preliminary activity aspect, the core activity aspect, and the closing activity aspect, with a percentage result of 95%, which is included in the "very good" category. 2) The participants' activities cover three aspects, namely aspects of preliminary activities, aspects of core activities, and aspects of closing activities, with a percentage of 90.5%, which is the "very good" category. 3) The results of learning in applying demonstration methods in training make banana products fall into the "very good" category, with a percentage reaching 100%. 4) The response of the training participants includes three aspects, namely the instructor aspect, the material aspect, and the activity aspect, with the results being 91% in the "very good" category.